2016
DOI: 10.1016/j.gaitpost.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of tibialis anterior tendon shortening in combination with calf muscle lengthening in spastic equinus in cerebral palsy

Abstract: The aim of this study was to evaluate the outcome of combined tibialis anterior tendon shortening (TATS) and calf muscle-tendon lengthening (CMTL) in spastic equinus. Prospectively collected data was analysed in 26 patients with hemiplegic (n=13) and diplegic (n=13) cerebral palsy (CP) (GMFCS level I or II, 14 males, 12 females, age range 10-35 years; mean 16.8 years). All patients had pre-operative 3D gait analysis and a further analysis at a mean of 17.1 months (±5.6months) after surgery. None was lost to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…12,13,29,33 The main goal in children with CP is to avoid a decrease of muscle strength of the triceps surae resulting in calcaneal gait and to strengthen the antagonists (eg, tibialis anterior muscle). 37 It is not clear, so far, if adults with CP show similar results after correction of equinus. Furthermore, compared with children, further growth cannot influence the postoperative course of rehabilitation.…”
mentioning
confidence: 99%
“…12,13,29,33 The main goal in children with CP is to avoid a decrease of muscle strength of the triceps surae resulting in calcaneal gait and to strengthen the antagonists (eg, tibialis anterior muscle). 37 It is not clear, so far, if adults with CP show similar results after correction of equinus. Furthermore, compared with children, further growth cannot influence the postoperative course of rehabilitation.…”
mentioning
confidence: 99%
“…The overall number of included patients with CP in our study is 3595 patients and 4814 limbs/feet, ranging from 7 patients in the study of Goncalves et al [ 22 ] to 1147 patients in the study of Naidu et al [ 28 ]. Most of the included studies reported the data of patients with the spastic type of CP (15 studies) [ 6 , 7 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 35 ]. The age of CP patients among included studies ranged from a mean of 3.8 years (with SD of 2) in the study of Boulay et al [ 17 ] to 18.2 years (with SD of 9.9) in the study of Horsch et al [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall number of included patients was 3595, with 4814 affected limbs being analyzed. The prevalence of equinus foot among patients with cerebral palsy varied substantially among included individual studies, ranging from 10.9% [ 35 ] to 100% [ 7 , 17 , 18 , 19 , 20 , 23 , 26 , 27 , 29 , 31 ]. A total of 22 studies were included in the meta-analysis with an overall prevalence rate of equinus foot of 93% (95% CI: 71–99%; I 2 = 100%, p < 0.01) ( Figure 2 ).…”
Section: Prevalence Of Equinus Footmentioning
confidence: 99%
See 2 more Smart Citations